Cesarean Hysterectomy in Cases of Placenta Adhesiva Involving Urinary Bladder: Serial Cases Report - Anak Agung Ngurah Jaya Kusuma (Journal of Global Pharma Technology, 2020)
Background: Placenta adhesiva is an obstetrics complication with potentially high maternal and neonatal morbidity and mortality. Its incidence is increasing, but the management remains controversial. Antenatal diagnosis and method of delivery are the main issues. Many clinicians now prefer a conservative approach. While cesarean hysterectomy remains the method of choice in most cases, it still exposes women to torrential bleeding risk, with reported mean blood loss of 3.000-10.000 ml. We present four cases of placenta adhesiva with suspected urinary bladder involvement during antenatal care, which is managed with cesarean hysterectomy. Case Presentation: A 34 years old multigravida (G3P2A0) at 32-33 weeks gestational age (GA) and a-39 year’s old multigravida (G4P3A0) came to the clinic complaining of painless vaginal bleeding. In another case, a 38 years old multigravida was also referred from a regional hospital diagnosed with G5P2A3 32-33 weeks GA + antepartum bleeding (total placenta praevia) suspected placenta adhesiva. And the last case was A 24 years old multigravida, with known low-lying placenta for 20 weeks of GA. Greyscale Ultrasonography (US) showed placental implantation at anterior uterine corpus covering entire internal uterine ostium (IUO), seen multiple lacunas crossing the vesicouterine serous border and placental protrusion into the urinary bladder. The cesarean hysterectomy was performed in all cases by placental identification, preoperative bleeding control, and careful tissue resection, as proposed in the triple-P procedure. The cases show a promising outcome following CS hysterectomy in cases of placenta adhesiva involving urinary bladder. Conclusion: We recommend a comprehensive team approach for decision making and management of patients suspected of placenta adhesiva with careful preparation to avoid complications. Keywords: Placenta Adhesiva, Caesarean Hysterectomy, Urinary Bladder.